Obsessive-compulsive symptoms in Parkinson's disease. Issue 3 (1st March 2001) - Alegret, M; Junqué, C; Valldeoriola, F; Vendrell, P; Martí, M J; Tolosa, E
Abstract : To systematically investigate obsessive-compulsive traits in Parkinson's disease, patients were administered the Maudsley obsessional-compulsive inventory (MOCI) and a modification of the Leyton obsessional inventory (LOI) to a sample of non-demented and non-depressed patients with Parkinson's disease. Patients with severe Parkinson's disease showed more obsessive traits than normal controls in MOCI and LOI total scores, and in the "checking", "doubting", and "cleaning" subscales of the MOCI. By contrast, patients with mild disease did not differ from controls. A significant correlation was found between severity and duration of illness and MOCI total score. These results support the involvement of basal ganglia in obsessive-compulsive symptomatology. As patients with mild Parkinson's disease did not differ from controls, obsessive-compulsive disorder does not seem to be directly related to the initial nigrostriatal dopaminergic deficiency which causes clinical Parkinson's disease symptomatology. The appearance of obsessive symptoms could be related to the subset of neurochemical changes taking place at the level of the basal ganglia circuitry as disease progresses.